Stent graft implantation in an aortic pseudoaneurysm associated with a fractured Cheatham-Platinum stent in aortic coarctation. (27th August 2015) - Kuhelj, Dimitrij; Berden, Pavel; Podnar, Tomaž
Abstract: We report a case of aortic pseudoaneurysm associated with a fractured bare Cheatham-Platinum stent following stenting for aortic coarctation. These complications were recognised 6 years after the implantation procedure and were successfully managed by percutaneous stent graft implantation. Staged approach for stent dilatation might prevent development of aortic pseudoaneurysms. In addition, careful follow-up is warranted after stenting for aortic coarctation, particularly in patients with recognised aortic wall injury.